Optimizing the Role and Function of Managers in Tiered Supervisionat - Ruri Wulandari; Enie Novietasari; Hening Pujasari; Sri Herni Wigiarti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Supervision is an active and continuous process aimed at ensuring that employees carry out their duties and responsibilities optimally in accordance with applicable standards, through monitoring, guidance, and performance evaluation activities, both directly and indirectly. At Jakarta Barat x Hospital, the implementation of tiered supervision in the General Outpatient Installation still faces several challenges, such as the suboptimal involvement of head nurses in the supervision process and the lack of standardized evaluation instruments. This study aims to optimize the implementation of tiered supervision by designing a daily work plan for head nurses and developing applicable and measurable supervision tools. The method used is a case study approach through a pilot study. The study involved 16 nurse respondents, with data collected through questionnaires, interviews, and observations. The data were analyzed qualitatively and descriptively using a fishbone diagram for problem analysis, followed by priority setting, POA formulation with the POSAC approach, and implementation guided by Kotter’s eight-step change theory. The results show that systematic implementation of tiered supervision can enhance compliance with standard operating procedures, improve team communication, and ultimately raise the quality of patient care services. This optimization is expected to serve as a pilot model for strengthening the role of head nurses as frontline supervisors in nursing care units. The optimization of tiered supervision through structured daily work plans for head nurses and the development of measurable supervision tools significantly improves adherence to standard operating procedures, enhances team communication, and strengthens the overall quality of patient care. This approach not only clarifies the managerial role of head nurses as frontline supervisors but also provides a scalable model that can be replicated in other nursing units to ensure consistent, high-quality supervision and service delivery.